Earnings management by non-profit organisations: evidence from UK charities - Nguyen, Tam; Soobaroyen, Teerooven (Wiley, 2018)
Informed by stakeholder theory and resource dependence theory, this paper investigates whether United Kingdom (UK) charities are engaged in earnings management practices. Based on a sample of 1414 charities over a five-year period (2008–2012) this study firstly finds that UK charities use discretionary accruals to drive their financial results toward a zero surplus/deficit; this result also reveals that the distribution of reported earnings around zero is prevalent amongst UK charities. In addition, in contrast to prior findings, the empirical results point to a significant association between leverage and earnings management behaviour by charities. Lastly, this study also finds that the practice of earnings management is influenced by non-profit organizational size.